Gambaran Pengetahuan Dan Sikap Ibu Tentang Pemberian MP-ASI Dini Pada Bayi Usia 0-6 Bulan Di Wilayah Kerja Puskesmas Perawatan Namrole Tahun 2019 - Epi Dusra (SEKOLAH TINGGI ILMU KESEHATAN KESDAM IV DIPONEGORO, 2019)
MP-ASI is additional food given to babies after the age of six months until the baby is 24 months old. The purpose of this study was to describe the knowledge and attitudes of mothers regarding early complementary breastfeeding to infants aged 0-6 months in the working area of ??the Namrole Nursing Health Center in 2019. The research approach is descriptive analytic with a descriptive approach. The population in this study were all mothers who had toddlers aged 0-6 months in the working area of ??the Namrole health center, totaling 257 people. The sample size used was 156 people. The results showed that the mother's knowledge about MP-ASI in the working area of ??the Namrole Nursing Health Center showed that out of 156 mothers under five, most had knowledge about early MP-ASI in the sufficient category, namely 61 mothers under five (39.1%). While the results for the attitude of mothers about MP_ASI in the working area of ??the Namrole Health Center show that out of 156 mothers of toddlers, most of them had attitudes about early MP-ASI in the less category, namely 101 mothers of toddlers (64.7%). It was concluded that the mother's knowledge about early MP-ASI was identified by giving early MP-ASI to infants aged 0-6 months with the most categories namely sufficient and for the mother's attitude about early MP-ASI by giving early MP-ASI to infants aged 0-6 months with the most less categories found in this study.